Analisis Konsep Tarbiyah Ta’lim dan Ta’dib dalam Perspektif Tafsir Al-Qur’an - Sri Wahyuni Harahap; Asnil Aidah Ritonga; Ahmad Darlis; Hotmasarih Harahap (Instructional Development Journal, 2022)
This study aims to clarify the differences in several terms in the concept of Islamic education in accordance with the verses of the Qur'an and the interpretation of the verses. There are many terms that are often used in the concept of Islamic education, but many do not know that each term used has a different meaning. Some of the educational concept terms that will be discussed in this study are the terms tarbiyah, ta'lim and ta'dib. This study uses a literature study research method taken from several books, commentaries and journals.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//